COMPETENCE-BASED APPROACH FOR SYSTEM STAFF EVALUATION IN AN ORGANIZATION - Vasily S. Kasyanov; Ksenia N. Balastrova (Вестник Северо-Кавказского федерального университета)
The article discusses main approaches to identifying and implementation of competence-based model of staff evaluation. The current competence models used in various organizations are described and enhanced in subjective and objective aspects of its formation. Main problems rised while implementation competence-based approach have analyzed and proposed most adequate ways to solve them.